PSIKOEDUKASI MENUMBUHKAN EMPATI SOSIAL DI KALANGAN MAHASISWA POLTEKNAKER CIRACAS - Tumanggor, Raja Oloan; Yulinta, Helpani; Farida Putri, Nurfathiyyah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This article discusses the application of psychoeducation to foster social empathy among students at the Ciracas Employment Polytechnic in East Jakarta. The psychoeducational methods used included interactive presentations, discussions, and experience sharing. The results of the psychoeducation showed a significant increase in students' social empathy levels after participating in the psychoeducation, characterized by greater emotional awareness and understanding of others' feelings. Psychosocial education plays a crucial role in developing empathy as social capital on campus.